Nanocluster metal oxide catalyst for lignin oxidation to platform chemicals / Mariom Zamila Shilpy - Mariom Zamila, Shilpy (2016)

(untitled)
This study involves the valorization of model compound of lignin, a naturally abundant bio-polymer, to harness benefit in terms of chemicals and energy source for human utilization. Mixed metal cobalt titanium oxides CoTiO3 and composite with titania CoTiO3/TiO2 were prepared by solution phase method and applied for the liquid phase catalytic oxidation of a lignin model compound, vanillyl alcohol to vanillin. The morphology, phase composition and crystal structure of the freshly prepared and reused CoTiO3 and CoTiO3/TiO2 catalyst were studied by using scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and Raman spectroscopy. The analysis supported properties of optimal heterogeneous catalyst in lieu of their phase composition, generation of highly dispersed metallic cobalt and high surface. The oxidation process of vanillyl alcohol used H2O2 as an oxygen source. The vanillyl alcohol conversion was influenced by various experimental conditions such as reaction time, temperature, molar ratio of reactants, catalyst loading, nature of solvent and reaction medium. The bimetallic oxide catalysts were synthesized efficiently to perform the high conversion and selective oxidation of vanillyl alcohol into fine chemicals, such as vanillin and vanillic acid. In the presence of NaOH in acetic acid and isopropanol solvents, the CoTiO3 catalyst exhibits remarkable conversion of 99% and excellent selectivity of 99.8% to vanillin, respectively. On the other hand, in the case of CoTiO3/TiO2 catalyst, the highest conversion (99%) was registered in the acetic acid as a solvent with presence of NaOH while without catalyst the recorded conversion was 80%. These could be attributed to the formation of peracetic acid. The oxidation reaction mechanism over the catalyst was postulated based on the analysis of products using high performance liquid chromatography (HPLC) analysis. It has been discovered that CoTiO3 and CoTiO3/TiO2 catalyst can retain its performance without significant change in the catalytic activity after four consecutive cycles.